Liraglutide, 7,8-DHF and their co-treatment prevents loss of vision and cognitive decline in a Wolfram syndrome rat model - Kadri Seppa (Nature Portfolio, 2021)
Abstract Wolfram syndrome (WS) is a monogenic progressive neurodegenerative disease and is characterized by various neurological symptoms, such as optic nerve atrophy, loss of vision, cognitive decline, memory impairment, and learning difficulties. GLP1 receptor agonist liraglutide and BDNF mimetic 7,8-dihydroxyflavone (7,8-DHF) have had protective effect to visual pathway and to learning and memory in different rat models of neurodegenerative disorders. Although synergistic co-treatment effect has not been reported before and therefore the aim of the current study was to investigate liraglutide, 7,8-DHF and most importantly for the first time their co-treatment effect on degenerative processes in WS rat model. We took 9 months old WS rats and their wild-type (WT) control animals and treated them daily with liraglutide, 7,8-DHF or with the combination of liraglutide and 7,8-DHF up to the age of 12.5 months (n = 47, 5–8 per group). We found that liraglutide, 7,8-DHF and their co-treatment all prevented lateral ventricle enlargement, improved learning in Morris Water maze, reduced neuronal inflammation, delayed the progression of optic nerve atrophy, had remyelinating effect on optic nerve and thereby improved visual acuity in WS rats compared to WT controls. Thus, the use of the liraglutide, 7,8-DHF and their co-treatment could potentially be used as a therapeutic intervention to induce neuroprotection or even neuronal regeneration.